A factor analysis of academic and socio-demographic determinants of students’ achievement interest in Indonesia - Daniar Setyo Rini; Eka Putri Azrai; Fitria Pusparini; Annisa Ramadhani; Ade Nurul Hikmah (Universitas Muhammadiyah Malang, 2025)
The demands of 21st-century skills in the digital era have driven curriculum reforms in Indonesia, including the implementation of the Merdeka Curriculum, which promotes knowledge sharing and encourages students to enhance both academic and non-academic achievements. However, challenges in its implementation have emerged, particularly students’ low participation in achievement-related activities. The purpose of this study is to identify what factors affect students' interest in achievement. This study uses a survey method with a quantitative and qualitative approach. A total of 212 students from 16 public universities and 14 private universities were sampled in this study. Quantitative data collection used three questionnaires, namely work engagement questionnaires for students, deep learning questionnaires, and achievement interest questionnaires. Thematic analysis is used for qualitative data. Based on data analysis, 5 component factors were obtained from the 11 variables tested, including the 1st factor, namely the variables of academic engagement and deep learning (intrinsic academic factors); Factor 2nd: parental educational background; 3rd factor: tribal or cultural background of parents; 4th factor: gender; and the 5th factor: mother's work. Factor 1 (academic intrinsic) significantly had a positive correlation of 3.9% to students' interest in achievement.